2023
DOI: 10.3390/dj11110258
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and Predictability of Coronal Maxillary Expansion Repercussion with the Aligners System: A Retrospective Study

Ana Sofia Rocha,
Maria Gonçalves,
Ana Catarina Oliveira
et al.

Abstract: The Invisalign® system (SmartForce® G8) aims to guarantee aesthetics and provide good orthodontic treatment results. Dentoalveolar expansion is possible with clear aligners and can be used to correct dentoalveolar crossbite, resolve crowding or modify the arch shape. Despite the treatment’s effectiveness, there is still disagreement among professionals concerning its true clinical potential. This study aimed to analyze the effectiveness and predictability of coronal tooth expansion movement in permanent dentit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…This also accounts for a current study likewise dealing with expansion efficiency and propagating that torque compensation should be implemented in the planning to enhance torque control during arch expansion, which also applied finite element analysis and only objected the upper jaw [ 30 ]. Another very recent study evaluated aligner performance regarding the efficiency and predictability of expansion, here in a retrospective study like ours likewise comparing maxillary and mandibular pre-treatment, planned treatment and post-treatment models [ 31 ]. They found that the greatest expansion was found in both the upper and lower premolars, and that aligners are effective for simultaneous intraoral expansion in both jaws.…”
Section: Discussionmentioning
confidence: 99%
“…This also accounts for a current study likewise dealing with expansion efficiency and propagating that torque compensation should be implemented in the planning to enhance torque control during arch expansion, which also applied finite element analysis and only objected the upper jaw [ 30 ]. Another very recent study evaluated aligner performance regarding the efficiency and predictability of expansion, here in a retrospective study like ours likewise comparing maxillary and mandibular pre-treatment, planned treatment and post-treatment models [ 31 ]. They found that the greatest expansion was found in both the upper and lower premolars, and that aligners are effective for simultaneous intraoral expansion in both jaws.…”
Section: Discussionmentioning
confidence: 99%